Pengoptimuman pra-olahan air sisa kilang kelapa sawit (pome) menggunakan kaedah elektro-penggumpalan - Ahmad Taib, Jamilullail (2013)
Palm oil industry is one of the industries that contribute pollution in Malaysia. The discharge of palm oil mill effluent (POME) which contains organic materials is the main cause of serious water pollution in Malaysia. Nowadays, electro coagulation treatment systems are widely used to treat water and wastewater. The purpose of this study was to determine the effectiveness of electro-coagulation treatment in treating palm oil mill wastewater. This study examines the characteristics of POME collected from an oil palm mill in Kahang, Johor. This study also examines the optimum conditions of the removal of pollutants in POME such as in the effects of current density, effective distance between the electrodes, pH and deposition time. In addition, the efficiency of the treatment was determined by analyzing the particle size after treatment. Two types of electrodes are used in these studies which are aluminum and iron. The study also looked into the effects of electro coagulation treatment system for the removal of COD, ammonia nitrogen, suspended solids and color from POME samples. The electro coagulation experiments were conducted using 4-liter volume glass reactor and the samples were electrolyzed by direct current power supply for 30 minutes. Experimental results show that the Al-Al pair plate achieved the optimum conditions of current density, distance between electrodes, pH and deposition time respectively at 70.7 A/m , 5 cm, pH 4 and 30 minutes. Al-Al plates successfully remove 81.4%, 83%, 84.7% and 90.4% respectively of COD, ammonia nitrogen, suspended solids and color at the optimum condition. Fe-Fe plate pairs showed optimal conditions achieved at 53.3 A/m 2 2 , 10 cm, pH 4 and 15 minutes respectively for the current density, distance between electrodes, pH and deposition time. COD, ammonia nitrogen, suspended solids and color successfully removed as much as 81.4%, 92.6%, 95.6% and 77.9% respectively. The combination of Al-Fe plates showed 80.7% COD, 86.3% AN, 88.1% SS and 89.6% Color were removed in the optimum condition. The current density, distance between electrodes, pH and deposition time achieved at 53.3 A/m , 5 cm, pH 4 and 15 minutes respectively. The combination of Fe-Al pair plate showed the same optimum conditions on the use of Al-Fe plate pairs. Removal of COD, ammonia nitrogen, suspended solids and color respectively by 82.9%, 88.3%, 87.2% and 90.3% was achieved. Particle size analysis showed that on the average size of the particles before treatment was 20 microns. Doses of 500, 1000, 2000, 2500 and 3000 mg / L Al2SO4, respectively resulted in flock sizes of 96, 101, 113, 116 and 86 μ for Al-Al pair plate. In addition, mixing the same dose of coagulant in POME resulted in particle size of 73, 86, 92, 126, 105 and 101 μ, respectively. In general, the results showed that the electro coagulation treatment system is capable of treating POME and can be an alternative treatment for the palm oil industry.